Strategi Penanaman Pendidikan Karakter Dalam Meminimalisir Bullying Siswa Sekolah Dasar. - Siti Annisa Jumarnis; Jehan Chantika Anugerah; Yulvani Juniawati Sinaga (Elementary Teacher Education Program, Majalengka University, 2023)
This study aims to identify strategies to minimize bullying in elementary school students. This research is a literature study applying qualitative descriptive analysis. The data source used comes from scientific articles published from 2017-2023 which are indexed by SINTA. Articles were collected via Google Scholar with the keywords character education, bullying, elementary school. Strategies to minimize bullying can be carried out through the application of character education, namely by carrying out activities of religious values, integrating character education in Civics and Social Studies subjects, school culture, outreach with topics of discussion on the causes of bullying, the impact of bullying and how to prevent bullying, and creating schools that comfortable. The strategy of instilling character education contributes to reducing the number of bullying that occurs in elementary school students.